GERM PLASM DIVERSITY OF GROUNDNUT BASED ON THE CHARACTER OF MORPHOLOGY, RESULT, AND OIL CONTENT - Zulchi, Try; Kurniawan, Hakim; Afza, Higa; P, Husni; M, Agus; Nurul, Ana (University of Muhammadiyah Malang, 2016)
Groundnut is one of the largest vegetable oil and has a good nutritional value. It could be used as an alternative source of food, industrial raw materials, and bioenergy. The main function of fats and oil in seeds reserves source of energy. This research aims to study the diversity of morphological, yield, and the oil content in groundnut germplasm. The planting of groundnut was conducted at the experimental station Cikeumeuh BB Biogen Bogor from July until December in 2013, with the germplasm of groundnut as much as 200 accessions. The characters identification is determined by the method of morphological characterization with Groundnut Descriptor from IPGRI. Analyze oil content of groundnut used soxhlets method at the Laboratory of Post-harvest Bogor. The results showed that germplasm groundnut have varied levels of diversity at characters. Relatively high morphological diversity founded the character of pod yield/plot, weight of pods/plant and number of immature pods. Groundnut oil content is range 33% to 47%. There are a real positive correlation between the number of pods to variable morphology, yield and oil content, but negatively correlation at weight of 100 seeds. Number of pods and number of branches is positively correlation with oil content of groundnut seeds. Cultivars groundnut that have the characters of promise could be used as national asset and the source of genes as a parent in the breeding program.Â Keywords: Diversity, Groundnut, Morphology, Oil Content